BUSINESS INCOME IN RELATION TO PRODUCTION RISK CASE STUDY: DAIRY CATTLE FARMING BUSINESS IN CISARUA DISTRICT, BOGOR REGENCY, WEST JAVA PROVINCE - Noviana, Rosita; Dian, Prasmita (Jurnal AGRISEP, 2022)
Cisarua District produces the least amount of cow's milk among numerous cows' milk production centers in Bogor Regency. Additionally, the fluctuations in milk production caused by disease in dairy cattle are also known to occur in Cisarua District. The study aimed to determine the expected business income when a production risk exists. The cross-sectional data used in this study were obtained from 57 dairy cattle farmers with an average number of 4 lactating cows consisting of second lactating cows, third lactating cows, and pregnant cows. Business income was calculated using R/C ratio analysis, and the expected value of income when production risk exists was measured using expected return. The expected return value was positive, which was IDR 1,907,582. The value represents dairy cattle farmers were risk takers because they continued to run the dairy cattle farming business when a production risk existed. The probability of disease as a production risk factor demonstrated that the dairy cattle farming business in Cisarua District remained profitable.